ChemInform Abstract: Synthesis and Anticancer Evaluation of Novel 9α‐Substituted‐13‐(1, 2, 3‐triazolo)‐parthenolides. Issue 41 (September 2016) - Zaki, Mohamed; Allouchi, Hassan; El Bouakher, Abderrahman; Duverger, Eric; El Hakmaoui, Ahmed; Daniellou, Richard; Guillaumet, Gerald; Akssira, Mohamed
Abstract: The diastereoselective Michael addition of TmsN3 to parthenolide (I) gives the key intermediate (III), which undergoes regioselective 1, 3‐dipolar cycloaddition with various alkynes affording triazole derivatives.